2017
DOI: 10.11606/issn.2316-9079.v16i1p3-11
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of the critically endangered salamander Ambystoma leorae (Caudata: Ambystomatidae) from the Río Tonatzin, Mexico

Abstract: Natural history of the critically endangered salamander Ambystoma leorae (Caudata: Ambystomatidae) from the Río Tonatzin, Mexico. In Mexico, many species of Ambystoma are endangered, but unfortunately little is known about their natural history and ecology. We report on aspects of the natural history of A. leorae, a critically endangered endemic salamander, from the Río Tonatzin, State of México, Mexico. We observed egg masses, which were attached to vegetation, from April to June, with a mean of 7.28 eggs per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…Some Ambystoma species are considered obligate paedomorphs which never go through metamorphosis, and others are considered facultative paedomorphs which can metamorphose under certain conditions to transform from aquatic larvae to terrestrial adults (Everson et al ., 2021). Ambystoma altamirani is a facultative paedomorphic salamander with a distribution restricted to the high mountain streams of Central Mexico (Lemos‐Espinal et al ., 1999, 2016; Woolrich‐Piña et al ., 2017; IUCN, 2020). This species is considered threatened by Mexican law (NOM‐059, SEMARNAT, 2015) and Endangered by the IUCN (IUCN, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some Ambystoma species are considered obligate paedomorphs which never go through metamorphosis, and others are considered facultative paedomorphs which can metamorphose under certain conditions to transform from aquatic larvae to terrestrial adults (Everson et al ., 2021). Ambystoma altamirani is a facultative paedomorphic salamander with a distribution restricted to the high mountain streams of Central Mexico (Lemos‐Espinal et al ., 1999, 2016; Woolrich‐Piña et al ., 2017; IUCN, 2020). This species is considered threatened by Mexican law (NOM‐059, SEMARNAT, 2015) and Endangered by the IUCN (IUCN, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This species is considered threatened by Mexican law (NOM‐059, SEMARNAT, 2015) and Endangered by the IUCN (IUCN, 2020). Populations of A. altamirani are subject to many threats such as urbanization, pollution, land‐use change, the introduction of invasive fish, and diseases (Lemos‐Espinal et al ., 1999, 2016; Frías‐Alvarez et al ., 2008; Basanta et al ., 2021). Because gilled and non‐gilled individuals stay in or near aquatic habitats throughout their entire life (Lemos‐Espinal et al ., 1999; Camacho et al ., 2020), the presence of aquatic pathogens such as B. dendrobatidis may pose a substantial risk to populations' health, and may differentially affect gilled and non‐gilled individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Ocupa un área de distribución aproximada de 985,900 km 2 . En ambos estados se reportaron bajas densidades poblacionales entre los años 1985 y 1999, de entre cuatro y 59 individuos; actualmente la población, que parece ser la más estable y abundante, se encuentra en el Monte Tláloc dentro del Parque Nacional Iztaccíhuatl-Popocatépetl (PNIP), donde se han reportado hasta 223 individuos (Sunny et al, 2014b;Monroy-Vilchis et al, 2015;Lemos-Espinal et al, 2017).…”
Section: Método De Evaluación De Riesgo De Extinción De Especies Silvestresunclassified
“…For example, larval A. texanum select the substrate that is most similar to their body color . Substrate color is a significant factor in determining the presence or absence of A. leorae (Taylor, 1943) in sites along the Río Tonatzin in the state of México (Lemos-Espinal et al 2017), and a previous study found that Ambystoma altamirani Dugès, 1895 in the Arroyo los Axolotes used black substrates more than expected and white-yellow sites less than expected (Lemos-Espinal et al 2016).…”
Section: Introductionmentioning
confidence: 96%